THE DEADLY NURTURING ACT: AN ECOFEMINIST READING OF KRISTIN HANNAH’S THE GREAT ALONE - Syahroni, Wahyu Nur (Metahumaniora, 2023)
In the scope of ecological-themed literature, many argue that female figures are closely related to the essence of nature rather than men due to some particular feminine features like giving birth and the act of nurturing. Another similarity between these two notions is their inferior positions in modern patriarchal societies where men dominate both nature and women. A text that possibly bears this particular issue between women, nature, and men is Kristin Hannah’s The Great Alone (2018). The text follows the story of Ernt Allbright’s family that moves from Seattle to the wilderness of Alaska. Throughout the story, the physical environment of Alaska plays a vital role in the progression of the conflicts between the characters. Hence, this research attempts to analyze the hierarchy between men, women, nature, and culture in The Great Alone. In analyzing the topic within the object of this study, Plumwood’s theory of dualism is used as the primary framing tool. In motion with Plumwood’s dualism, this research uses qualitative descriptive method and close reading technique as the main strategy to collect the data from the object. The results show that both women and nature are still considered inferior beings from the perspective of the main male character. However, the chronological conflicts of the story show that women and nature are the ones that reside on the dominant side.